PENILAIAN DAYA TARIK OBJEK WISATA ALAM RIAM ANGAN TEMBAWANG DI DESA ANGAN TEMBAWANG KECAMATAN JELIMPO KABUPATEN LANDAK - Aristo, Aristo; Rifanjani, Slamet; Latifah, Siti (Universitas Tanjungpura, 2020)
Riam Angan Tembawang Village is located in Jelimpo District, Landak Regency, West Kalimantan Province. Angan Tembawang Village has interesting natural tourism to visit, such natural objects are rivers and waterfalls and are called Riam Angan Tembawang. This study aims to determine the natural tourist attraction of Riam Angan Tembawang Village, Jelimpo District, Landak Regency. This research was conducted by the descriptive method. Data obtained by direct interviews with respondents about the attractiveness of attractions and fill out a list of questions. The results of the calculation of all the assessment criteria for attraction of Riam Angan Tembawang attraction as well as the elements and sub-elements, namely natural beauty 26,66%, the uniqueness of natural resources 22,36 %, the amount of potential natural resources 22,22 %, natural resource 26,63 %, sensitivity of natural resources 17,08 %, types of nature tourism activities 28,33 %, air cleanliness and location no effect 25,77 %, vulnerability of encroachment and the fire 11,11 %. All elements of attraction assess by the Riam Angan Tembawang tourism are 1.080,96 and this area has good area attractions (B) to be developed into a tourist attraction.Keywords: attraction, nature, riam angan tembawang, tourist attraction.